Restoring Teeth with an Advanced Lithium Disilicate Ceramic: A Case Report and 1-Year Follow-Up. (16th September 2022) - Hölken, Felicitas; Dietrich, Helmut
Abstract : Advancements in materials science and bonding protocols as well as new manufacturing methods foster the development of novel ceramic materials to meet the increased demands for highly aesthetic, biocompatible, and long-lasting restorations in fixed prosthodontics. This case report highlights the minimally invasive rehabilitation with a new advanced lithium disilicate (ALD) ceramic block. It is reinforced with virgilite crystals in managing esthetic demand of patient besides having a high flexural strength. According to the manufacturer, the material provides a biaxial strength measured at >700 MPa and improved optical properties. The remarkable speed sintering time of approx. 4.5 minutes makes processing very fast. Time efficiency, predictability, and economically interesting treatment options are of great importance in current dentistry and can be well implemented in CAD/CAM dentistry. The newly introduced ALD ceramic for the "Chairside Economical Restoration of Esthetic Ceramics"/"CEramic REConstruction" (CEREC) system produces an esthetically pleasing and clinically excellent restoration. The shorter processing time combined with high flexural strength will optimize the chairside workflow. New treatment indication options for lithium disilicate ceramics will expand. Although more evidence from long-term clinical studies is needed to verify the clinical performance and manufacturer recommendations regarding indication, preparation and cementation must be followed very strictly. In the present case report, restorations were indicated for seven posterior teeth, which were prepared, scanned, designed with CEREC-Primescan SW 5.1.3, and fabricated with MCX5. The monolithic restorations were placed adhesively. The rehabilitation with the ALD blocks resulted in an aesthetically pleasing, functional outcome that improved overall treatment time and increased patient and practitioner satisfaction, which remained stable over a one-year follow-up period.